PENERAPAN METODE PEMBELAJARAN PQ4R UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI SMA MUHAMMADIYAH 1 METRO - Triani Ratnawuri; Ahkaf Fikri; Siti Suprihatin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The development of science and technology is growing rapidly. This requires the existence of quality human beings so as to be able to create new innovations and be able to face competition. Education is a pursuit of school for children and adolescents who are handed over to them to have perfect skills and full awareness of their social relationships and tasks. The 2013 curriculum goal is to prepare Indonesian people to have the ability to live as the individu and citizens who are faithful, productive, creative, innovative, and affective and able to contribute to the life of society, nation, state and world civilization. The problem formulation of this class action research is how is the effect of the application of PQ4R learning methods to improve learning outcomes of economic subjects at XI grade students of Senior High School Muhammadiyah 1 Metro". The purpose of the study was to determine the effect of the application of the PQ4R learning method and to improve learning outcomes of economic subjects in class XI of Muhammadiyah 1 Metro High School "and the benefits of classroom action research were seen from two parties in terms of theoretical and practical aspects. The action hypothesis in this class action research through the use of PQ4R learning methods (preview, question, read, reflect, recite, review), to improve the economic learning outcomes of class XI students of Muhammadiyah 1 Metro High School. The application of the PQ4R method in learning economics at XI grade of Senior High School Muhammadiyah 1 Metro can increase teacher and student activity. It can be seen from the average score of teacher activity in cycle I, namely 41.16 with the category "sufficient", in the second cycle increased to 45.83 with the category "good" with a difference of 4.67. Likewise, the average score of the first cycle of student activity is 41.16 with the category "enough", in the second cycle increased to 46, 99 with the "good" category with a difference of 5.83. So it can be concluded that by applying the learning model Preview, Question, Read, Reflect, Recite, Review (PQ4R) can increase student learning outcomes of economic subjects at XI grade of Senior High School Muhammadiyah 1 Metro.Keywords: PQ4R Learning, Learning Outcomes